Three-Month Specialized Advanced Course on Sociolinguistics, 7 June - 4 September 1976 : course project : towards an ethnography of communication in oral literature a conceptual framework based on the etic-emic distinction - Lazaro, Patrocinio B. (RELC, 1976)
"The present writer discusses a theoretical model that shows a configuration or pattern of approaches in the study of oral literature. From this model, he develops his own conceptual framework on the ethnography of communication based on the etic-emic approach or the micro-macro level of investigation in sociolinguistics. From an eclectic standpoint, the present writer also makes an attempt to apply his "etical" framework to a specific genre of Philippine folklore - a Tinguian folktale. By making a situation-collocution matrix of the folktale "A mortal ascends to the skyworld", he describes and classifies the speech event, the speech act, the speech function, and the role relationships that are involved in the manipulation of social-interactional strategies found in the text."